THE INFLUENCE OF ORGANIZATIONAL CULTURE, QUALITY OF HUMAN RESOURCES AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE OF BPJS KETENAGAKERJAAN MAKASSAR BRANCH OFFICES AND ITS RANGE OF BRANCH OFFICES - Gasali, Gasali; Gani, Ahmad; H.A, Ismail (Universitas Ichsan Sidenreng Rappang, 2025)
This research was conducted with the objectives of testing and analyzing the influence of organizational culture on performance; and testing and analyzing the influence of human resource quality on performance; and testing and analyzing the influence of job satisfaction on performance; and testing and analyzing the simultaneous influence of these three variables on employee performance at the Makassar Branch Office of BPJS Ketenagakerjaan and its Subordinate Branch Offices. This research used primary data with a sampling technique, namely the Total Sampling or Census method, through a survey of 90 employees working and assigned to the Makassar branch office and its subordinate branch offices. The survey was conducted from February 2026 to March 2026. Data were analyzed using SPSS 25. The results of this study indicate that Organizational Culture has a positive and significant influence on performance; and Human Resource Quality has a positive and significant influence on Performance; and Job Satisfaction has a positive and significant influence on Performance; Organizational Culture, Human Resource Quality, and Job Satisfaction simultaneously have a significant influence on Performance; of BPJS Ketenagakerjaan employees at the Makassar Branch Office and its associated branch offices. Overall, the results of this study indicate that Organizational Culture, Human Resource Quality, and Job Satisfaction are important factors contributing to improving the performance of BPJS Ketenagakerjaan employees at the Makassar Branch Office and its associated branch offices.